Psychosocial needs of women undergoing perinatal intimate examinations - Tshabalala, Ntsoaki M.; Yazbek, Mariatha; Maree, Carin (Health SA = SA Gesondheid, 2025)
Background: Intimate examinations are a vital part of midwifery care during pregnancy, labour, and the postnatal period. Women’s experiences of these procedures vary greatly, and poor communication can lead to significant distress, particularly for first-time mothers. Despite its importance, psychological health during such examinations is often overlooked. Aim: The study aims to explore the psychosocial needs of women undergoing perinatal intimate examinations. Setting: Data were gathered in postnatal wards and Midwife Obstetric Units (MOUs) of level 1/district hospitals within the Tshwane District, Gauteng province, South Africa. Methods: Telephonic semi-structured interviews were conducted with 30 postnatal mothers from two district hospitals and four MOUs located in community health centres in the Tshwane District. Results: Women expressed the need for competent, empathetic health care providers who create a respectful, safe, and dignified environment. Minimising the frequency of intimate examinations reduced both physical and emotional discomfort. The use of alternative, less invasive assessment techniques enhanced women’s comfort and alleviated anxiety. Emotional and practical support from health professionals and significant others also improved women’s overall experience, decreasing fear and embarrassment. Conclusion: Intimate examinations often evoke fear and embarrassment due to privacy concerns and past trauma. Women require psychosocial support during these procedures. Midwives should receive training to conduct examinations with sensitivity and care to ensure women’s comfort and emotional safety. Contribution: The study provides South Africa-specific guidelines promoting holistic, respectful perinatal intimate examinations that emphasise communication, consent, and women’s psychosocial well-being.